EVALUATION OF INSECTICIDAL POTENTIAL: A COMPARATIVE STUDY OF VACHA (Acorus calamus), APAMARGA (Achyranthes aspera), AND KEBUKA (Costus speciosa) EXTRACTS AGAINST PULSE BEETLE (Callosobruchus chinensis) IN STORED CHICKPEAS - Dr. Drakshayani N Benni; Dr. Satej Banne (The Bioscan, 2025)
This study investigates the insecticidal efficacy of Vacha (Acorus calamus), Apamarga (Achyranthes aspera), and Kebuka (Costus speciosus) extracts against the Pulse Beetle (Callosobruchus chinensis) in stored chickpeas (Cicer arietinum). Pulse Beetles are significant pests in stored legumes, causing extensive losses in seed quality and quantity. The objective was to evaluate the effectiveness of these plant-derived extracts as natural alternatives to chemical insecticides, aligning with the growing demand for eco-friendly pest management strategies. Key results indicated differential efficacy among the three plant extracts, with Acorus calamus showing the highest insecticidal activity, significantly reducing beetle infestation rates and seed damage. Achyranthes aspera demonstrated moderate effectiveness, while Costus speciosus) exhibited the least efficacy but still outperformed untreated controls. These findings were further discussed in the context of their active phytochemicals, such as alkaloids and essential oils, which disrupt the metabolic and reproductive systems of the pests. The study concludes that these botanical extracts are promising candidates for sustainable pest management. The novelty of this research lies in its comparative approach, highlighting the potential of traditional herbal knowledge in addressing modern agricultural challenges. This approach is particularly relevant in current times, where there is a pressing need to reduce the environmental and health impacts of synthetic pesticides while ensuring food security through effective pest control in stored grains.